Stabilising Potential of Sawdust Lignin based Extracts in Compressed Lateritic Bricks - Fadele, O.A; Ata, O.J. (Institute of Research and Community Outreach - Petra Christian University, 2018)
Lignocellulosic materials are abundant in nature, rich in some functional groups, considered less harmful to human health and the environment.The resulting waste may be recycled for other beneficial uses. Lignin is known to be a natural binder in lignocellulosic materials and several studies have confirmed it has binding ability with soil particles. This paper studied its stabilising potential in compressed lateritic bricks, especially its effects on density and compressive strength properties of the bricks. Lignin additives extracted from sawdust were used to stabilise laterite, while the bricks were moulded with the UNIFE ram, a type of the CINVA ram. The laterite was stabilised at 4%, 8% and 12%, while cement stabilised samples and 0% (unstabilised laterite) samples prepared accordingly were used as controls. The results showed that the LBAs contributed to the strength gained by the bricks at 3, 7, 14 and 28 days air curing, while the bricks samples were categorised as high density.